TINJAUAN PEMAHAMAN GURU BIOLOGI SMA NEGERI SE-KABUPATEN AGAM TERHADAP KURIKULUM 2013 TAHUN PELAJARAN 2014/2015 - Marlinda, Arwil - (STKIP PGRI Sumbar, 2014)
The background of this research is the teachers difficulty in designing lesson plans, the implementation of scientific approach and authentic assessment in curriculum 2013. The purpose of this research is to determine the level of biology teachers understanding about curriculum 2013 of SMAN Agam regency in academic year 2014/2015. The research is a descriptive research by using quantitative method. The sample in this research is 20 biology teachers who teach in SMAN Agam regency in academic year 2014/2015. In this research the validity of questionnaire tested by 3 validators. Furthermore, the data obtained by distributing questionnaires to the respondents. Based on the result of the research, it shows that the percentage of biology teachers understanding about curriculum 2013 of SMAN Agam regency in academic year 2014/2015 with an average of 79.62%. It can be concluded that the understanding of the biology teachers of SMAN Agam regency about curriculum 2013 is good.